The Use of Social Media as a Water Tourism Destination Promotional Media at Banjar Hot Spring: Digital Marketing Perspective - Putu Nata Kusuma; Trianasari Trianasari; Putu Indah Rahmawati (Universitas Pendidikan Ganesha, 2022)
This research aimed at exploring how social media was used to promote a tourist destination and how tourists perceive the related content of the social media. The study was conducted at the Tourism Department of Buleleng Regency and the tourism site of Banjar Hot Spring. To meet the fistt research objective, data were collected from three officers and a head of maketing division. The participants were recruited using purposive sampling technique with the criteria of having involvement in the management of social media. Data were collected using observation, interview, and focus group discussion. For the second research question, 38 tourists voluntarily participated. Data were gathered using open-ended-questions method. A qualitative approach was employed for data analysis. The findings suggested that the Tourism Department has demonstrated an optimal utilisation of social media to promote Banjar Hot Spring. However, the use of story telling and type writing may enhance the performance of social media. The second data analysis revealed that tourists perceived the social media was satisfactory.